REVITALIZING LOCAL CULTURE IN EDUCATION: INTEGRATING RIAU TRADITIONAL HOUSES INTO DIGITAL DESCRIPTIVE TEXT MATERIALS FOR JUNIOR HIGH SCHOOL - Siti Sundari; Elly Prihasti Wuriyani; Muharrina Harahap (Curricula: Journal of Teaching and Learning, 2024)
The innovation of FlipHtml5 digital-based teaching materials integrated with the local wisdom of Riau traditional houses for VII grade students of SMP Negeri 3 Rambah Hilir is an effort to improve student learning outcomes, especially on descriptive text material in grade VII Indonesian language learning. This study aims to determine the effectiveness and feasibility of Fliphtml5 digital-based descriptive text teaching materials integrated with the local wisdom of Riau Traditional Houses for Class VII Students of SMP Negeri 3 Rambah Hilir. This research uses Research and Development (R&D) with the ADDIE model which consists of analysis, design, development, implementation, and evaluation. The sample used in this study was 32 seventh grade students of SMP Negeri 3 Rambah Hilir. Observation, interviews, documentation, questionnaires and student learning outcomes test sheets are some of the data collection techniques in this study. The instrument used to assess the feasibility of teaching materials in this study is a product validation questionnaire for material experts, design experts, teacher responses, student responses as well as a pre-test and post-test for students. The results of the feasibility of teaching materials Validation of material experts obtained a feasibility percentage of 97.5% with the criteria “Very Feasible”, design experts obtained a feasibility percentage of 97.3% with the criteria “Very Feasible”. The feasibility results of teaching materials obtained from the results of teacher responses amounted to 97.6% with the criteria “Very Feasible” and the results of the feasibility of teaching materials obtained by the teacher.